Dissociable components of cognitive control: an event-related potential (ERP) study of response inhibition and interference suppression. - Christopher R Brydges (Public Library of Science (PLoS), 2012)
Background Cognitive control refers to the ability to selectively attend and respond to task-relevant events while resisting interference from distracting stimuli or prepotent automatic responses. The current study aimed to determine whether interference suppression and response inhibition are separable component processes of cognitive control. Methodology/principal findings Fourteen young adults completed a hybrid Go/Nogo flanker task and continuous EEG data were recorded concurrently. The incongruous flanker condition (that required interference suppression) elicited a more centrally distributed topography with a later N2 peak than the Nogo condition (that required response inhibition). Conclusions/significance These results provide evidence for the dissociability of interference suppression and response inhibition, indicating that taxonomy of inhibition is warranted with the integration of research evidence from neuroscience.